2010
DOI: 10.1007/s12374-010-9123-x
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid, Benzenoid, and Phenylpropanoid Compounds in the Floral Scent of Vanda Mimi Palmer

Abstract: Vanda Mimi Palmer is the product of a cross between Vanda Tan Chay Yan and Vanda tessellata. The flower of this hybrid produces a sweet-smelling fragrance during day time at the open-flower stage. This study aimed to investigate the floral scent constituents in Vanda Mimi Palmer. Scent emission analysis of this orchid was carried out at different time points in a 24-h cycle and also at different floral developmental stages. A comparison was also made on the volatiles emitted by Vanda Mimi Palmer and both of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 20 publications
4
32
0
Order By: Relevance
“…Cytochrome p450 proteins have been reported to be involved in the modification of monoterpene compound into another compound, for example conversion of linalool to linalool oxide (Hsiao et al 2006;Dudareva et al 2004;Dudareva and Pichersky 2000). Thus, VMPCyP450 was postulated to be involved in the fragrance biosynthesis pathway of Vanda Mimi Palmer since linalool oxide was detected as one of the volatiles of (Kim et al 2008) Vanda Mimi Palmer (Mohd-Hairul et al 2010). Besides, cytochrome p450 has been reported to be involved in other fragrance biosynthesis pathways including benzenoid/phenylpropanoid and lipoxygenase pathways (Ehlting et al 2006).…”
Section: Relative Expression Analysis Of Vmpcmek and Vmpcyp450 Transcmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome p450 proteins have been reported to be involved in the modification of monoterpene compound into another compound, for example conversion of linalool to linalool oxide (Hsiao et al 2006;Dudareva et al 2004;Dudareva and Pichersky 2000). Thus, VMPCyP450 was postulated to be involved in the fragrance biosynthesis pathway of Vanda Mimi Palmer since linalool oxide was detected as one of the volatiles of (Kim et al 2008) Vanda Mimi Palmer (Mohd-Hairul et al 2010). Besides, cytochrome p450 has been reported to be involved in other fragrance biosynthesis pathways including benzenoid/phenylpropanoid and lipoxygenase pathways (Ehlting et al 2006).…”
Section: Relative Expression Analysis Of Vmpcmek and Vmpcyp450 Transcmentioning
confidence: 99%
“…In Vanda Mimi Palmer, volatile analyses using GC-MS showed that the fragrance emission profile of this orchid was at the highest level in the early afternoon and dominated by terpenoid (ocimene and linalool), benzenoid (benzyl acetate and methylbenzoate), and phenylpropanoid (phenylethanol and phenylethyl acetate) compounds (Mohd-Hairul et al 2010). So far, only one fragrancerelated cDNAs has been isolated and characterized from Vanda Mimi Palmer, which is 1-deoxy-D-xylulose 5-phosphate reductoisomerase (VMPDXR) (Chan et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Although it is known that the color of a flower is the first and foremost cue for pollinator s attraction, odors may play a major role for their visits, both as long range attraction cues and at short distances as orientation cues among different flower parts or among different flowers 1,2 . The correct landing site and orientation of pollinators are very important requirements for an effective pollination, as demonstrated by the so-called honey-guides and other colored floral structures 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Don., is a famous ornamental potted plant cultivated in Malaysia selectively for its fragrance characteristic [3,4]. Mohd-Hairul et al [5] found that the floral scent of V. Mimi Palmer was predominated by terpenoid, benzenoid, and phenylpropanoid compounds using GC-MS analyses (Table 1).…”
Section: Introductionmentioning
confidence: 99%